2004
DOI: 10.1161/01.cir.0000133311.25587.de
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD34-Positive Cells Provide an Index of Cerebrovascular Function

Abstract: Background-Increasing evidence points to a role for circulating endothelial progenitor cells, including populations of CD34-and CD133-positive cells present in peripheral blood, in maintenance of the vasculature and neovascularization. Immature populations, including CD34-positive cells, have been shown to contribute to vascular homeostasis, not only as a pool of endothelial progenitor cells but also as a source of growth/angiogenesis factors at ischemic loci. We hypothesized that diminished numbers of circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
140
4
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 8 publications
17
140
4
2
Order By: Relevance
“…Interestingly, we found that the number of EPCs gradually increased through day 7 after acute onset, remained significantly higher until day 14 and returned to baseline by day 28. Although an earlier study that included only a small group of patients had findings similar to the present study, 21 the authors did not investigate the dynamic change in circulating EPCs in patients with hemorrhagic stroke. Therefore, our findings are the first to suggest that EPCs are mobilized to the peripheral blood in response to vascular trauma and may enhance the repair of damaged vessels.…”
Section: Discussionmentioning
confidence: 44%
“…Interestingly, we found that the number of EPCs gradually increased through day 7 after acute onset, remained significantly higher until day 14 and returned to baseline by day 28. Although an earlier study that included only a small group of patients had findings similar to the present study, 21 the authors did not investigate the dynamic change in circulating EPCs in patients with hemorrhagic stroke. Therefore, our findings are the first to suggest that EPCs are mobilized to the peripheral blood in response to vascular trauma and may enhance the repair of damaged vessels.…”
Section: Discussionmentioning
confidence: 44%
“…The latter was determined using a newly developed method that enables quantification of few CD34 + cells in peripheral blood in a highly reproducible manner. After acute cerebral ischemia, mobilization of CD34 + cells from bone marrow has been shown in stroke patients (Taguchi et al, 2004a). Furthermore, transplantation of CD34 + cells (Taguchi et al, 2004b) and bone marrow cells (Borlongan et al, 2004a, b) has been shown to restore cerebral blood flow in experimental models of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown accelerated neovascularization after administration of CD34 + cells in an experimental model of stroke (Taguchi et al, 2004b), and observed a positive correlation between levels of circulating CD34 + cells and neovascularization (Yoshihara et al, 2008) and regional blood flow (Taguchi et al, 2004a) in patients with chronic cerebral ischemia. In addition, we have delineated a contribution of circulating CD34…”
Section: Introductionmentioning
confidence: 82%
“…The absolute number of CD34 + cells was calculated using the internal control. On the basis of our previous studies, the cumulative intraassay coefficient of variation of the measurement was 7.4% and test-retest intraclass correlation of the level of CD34 + cells is 0.88 (Taguchi et al, 2004a). For statistical analysis, JMP version 5.1J was used.…”
Section: Methodsmentioning
confidence: 99%